Network Pharmacology Approach to Understanding the Antidiabetic Effects of Pineapple Peel Hexane Extract - Pendong, Christa Hana Angle; Suoth, Elly Juliana; Fatimawali, Fatimawali; Tallei, Trina Ekawati (Heca Sentra Analitika, 2024)
The increased interest in exploring alternative treatments for type 2 diabetes mellitus is accompanied by a rise in the prevalence of type 2 diabetes mellitus. Pineapple peel is one of the by-products of pineapple fruit and is known to possess potential for anti-diabetic activity. In this study, the n-hexane extract of pineapple peel was analyzed using network pharmacology methods to ascertain its potential in treating type 2 diabetes mellitus. The GC-MS analysis of the n-hexane extract of pineapple peel revealed the presence of 42 compounds, with 8 of them considered safe as they met the Lipinski Rule of Five criteria for drug-likeness and were classified as safe with toxicity levels in classes IV and V. The pineapple peel extract targeted 55 proteins related to type 2 diabetes mellitus (DMT2), potentially affecting DMT2 through the AGE-RAGE pathway in diabetes complications and insulin resistance. Network pharmacology analysis identified five genes targeted by pineapple peel, namely MAPK1, JAK2, MAPK8, PRKCD, and PPARA. Among these genes, MAPK1 exhibited a higher overall score than the others. Apart from its role in diabetes, MAPK1 is also implicated in cancer.